Decentralized Voting System using Blockchain - Kranthi Kiran Reddy; Gutha Vijay Kumar; Sai Siddu Sirimulla; Chanan Singh; Chaithanya Kumar Reddy; Ponnapati Pranay Santosh Reddy (International Journal of Scientific Research in Science, Engineering and Technology, 2024)
This article explores the use and impact of voting using blockchain technology. As a result of mounting worries about the honesty and security of conventional  voting  methods,  especially  in  the  digital era, the study tackles the requirement for an open, impenetrable, and  robust  method  of  conducting elections. A decentralized application on a blockchain platform is designed and implemented using the technique, which makes use of smart contracts for voter registration, ballot generation, and vote counting. The viability of blockchain technology in guaranteeing voter anonymity, data  integrity, and  cryptographic security are  important discoveries. Online voting can be  done securely  and  digitally using  blockchain technology. It has great potential to reduce costs and increase voter turnout. Using Blockchain we can secure any application and work securely for that application. Therefore, cryptocurrency, healthcare, real estate, etc. Many applications use blockchain technology. *Blockchain technology encrypts votes,  preventing any  votes  from being tampered with. It allows voters to vote for a candidate only once. The system reduces labor costs and counting errors by  providing quick  access to  election results. This article explains solutions to solve the above problems. Our solution is to use an online voting system based on the Ethereum blockchain.   That's why we connect surveys to blockchain technology
Keywords: Decentralized; Blockchain; Ethereum; Online Voting